Women’s economic empowerment, participation in decision-making and exposure to violence as risk indicators for early childhood caries - Morenike Oluwatoyin Folayan; Maha El Tantawi; Ana Vukovic; Robert Schroth; Balgis Gaffar; Ola B. Al-Batayneh; Rosa Amalia; Arheiam Arheiam; Mary Obiyan; Hamideh Daryanavard; Early Childhood Caries Advocacy Group (BMC Oral Health, 2024)
9p